2017
DOI: 10.1038/ejcn.2017.149
|View full text |Cite
|
Sign up to set email alerts
|

Association of whole grain intake with all-cause, cardiovascular, and cancer mortality: a systematic review and dose–response meta-analysis from prospective cohort studies

Abstract: Our study shows that whole grain intake was inversely associated with risk of total, CVD and cancer mortality. Our results support current dietary guidelines to increase the intake of whole grains. Government officials, scientists and medical staff should take actions to promote whole grains intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 55 publications
0
53
0
4
Order By: Relevance
“…According to the Global Burden of Disease study from 2019, a high intake of sodium, and a low intake of whole grains and fruits were the leading dietary risk factors for death and disability-adjusted life years, of which low intake of whole grain was the leading risk among young adults (35) . Dietary fibre and whole-grain products connect to a multitude of health benefits, among them being a lower risk of high blood pressure and a lower concentration of Low-density lipoprotein-cholesterol (LDL), reduced risk of all-cause mortality as well as cardiovascular disease and cancer mortality (36)(37)(38) , of which high blood pressure before pregnancy is considered a risk factor for pre-eclampsia (39) . Milk and dairy products contribute between 60 and 80 % of the iodine intake in the Norwegian diet and are considered its most important source (40) .…”
Section: Discussionmentioning
confidence: 99%
“…According to the Global Burden of Disease study from 2019, a high intake of sodium, and a low intake of whole grains and fruits were the leading dietary risk factors for death and disability-adjusted life years, of which low intake of whole grain was the leading risk among young adults (35) . Dietary fibre and whole-grain products connect to a multitude of health benefits, among them being a lower risk of high blood pressure and a lower concentration of Low-density lipoprotein-cholesterol (LDL), reduced risk of all-cause mortality as well as cardiovascular disease and cancer mortality (36)(37)(38) , of which high blood pressure before pregnancy is considered a risk factor for pre-eclampsia (39) . Milk and dairy products contribute between 60 and 80 % of the iodine intake in the Norwegian diet and are considered its most important source (40) .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this would be the first study which was clarified the factors having an influence on "rice change". The novel points of our results were that the factors of changing type of rice were associated with unhealthy laboratory been associated with a lower risk of cardiovascular [1,2], Type 2…”
Section: Discussionmentioning
confidence: 75%
“…Observational epidemiology studies suggest that higher whole grain intake is associated with lower risk of all-cause, cardiovascular, and cancer mortality [1,2], type 2 diabetes [3], and inversely associated with BMI [4], independent of other dietary and lifestyle factors. Moreover, a systematic analysis of dietary risks from studies of 195 countries also reported that 11 million deaths and 255 million in disability-adjusted life-years (DALYs) were attributable to the low intake of whole grain, fruits, and high intake of sodium [5].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most widely consumed cereal grains, wheat is an important component of the diet, contributing significantly to the daily dietary fibre intake of both adults and children . Whole grains also play a protective function against chronic disease through the provision of other important nutrients, including protein, resistant starch, vitamins and minerals . The risk of dietary imbalances in individuals choosing to restrict or eliminate wheat, in what could be an unnecessarily restrictive diet, is high …”
Section: Introductionmentioning
confidence: 99%
“…9 Whole grains also play a protective function against chronic disease through the provision of other important nutrients, including protein, resistant starch, vitamins and minerals. [10][11][12] The risk of dietary imbalances in individuals choosing to restrict or eliminate wheat, in what could be an unnecessarily restrictive diet, is high. 13,14 Dietary investigations of those with coeliac disease following a gluten-free -and thus necessarily wheat-free-diet found that many fell short of dietary recommendations including intake of fibre, iron and B vitamins.…”
Section: Introductionmentioning
confidence: 99%